Formulation and Optimization of Atovaquone Micronized Suspension by Top-down Method - Kathpalia, Harsha; Das, Sukanya; Shidhaye, Supriya (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: The present work aimed to tackle the solubility issue of a Biopharmaceutics Classification System (BCS) II drug, Atovaquone. Methods: Formulation of micronized suspension of atovaquone was optimized by employing a 32 full factorial design keeping poloxamer 188 (wetting agent) and phospholipon 90H (stabilizer) as the influential variables affecting the dependent variables viz. particle size and polydispersity index (PdI). Selected formulations from the optimized design space were further evaluated for dissolution and the formulation exhibiting maximum dissolution within 120 min was selected. The optimized batch consisting of atovaquone (15%), poloxamer 188 (2%), phospholipon 90H (1%), glycerin (10%) in the aqueous vehicle was microfluidized. Results: The particle size of resultant suspension was Zavg = 1313 ± 40 nm and PdI =0.1± 0.05. The zeta potential of the final micronized suspension was 0.0555 mV which indicated steric stabilization of the particles. The micronized suspension was adsorbed on a mixture of Kollidon CL SF and Aerosil 200 (2:1) and then dried and passed through 40# sieve. Conclusion: The solid-state characterization of the formulation revealed that the crystalline nature of the drug was retained after the milling process. The saturation solubility and in-vitro dissolution of adsorbed micronized suspension were 2.3-fold times enhanced as compared to the pure drug suspension due to a reduction in particle size. The top-down approach can be employed to improve the poor aqueous solubility of atovaquone.
Keywords: Atovaquone; Micronized suspension; Microfluidization; Full factorial design; Solubility enhancement